1984
DOI: 10.1042/cs0670591
|View full text |Cite
|
Sign up to set email alerts
|

Intestinal Absorption of Calcium in Greyhounds: The Response to Intermittent and Continuous Administration of Human Synthetic Parathyroid Hormone Fragment 1–34 (Hpth 1–34)

Abstract: Long-term studies of gastrointestinal radio-calcium absorption were undertaken in adult greyhounds before and during two treatment regimes with human parathyroid hormone fragment 1-34 (hPTH 1-34). The results were correlated with plasma vitamin D metabolite levels and kinetic indices related to the balance of fluxes of calcium between plasma and the rapidly exchangeable calcium pools of bone. Compared with adult man, results obtained before treatment started showed lower indices of gastrointestinal calcium abs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

1985
1985
2018
2018

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 0 publications
1
2
0
Order By: Relevance
“…Further experience has confirmed that this trend is statistically highly significant [5]; and similar results were seen in normal greyhounds given the same treatment [6]. However, when given in this way alone, in contrast to our findings in dogs [7], hPTH 1-34 did not increase dietary calcium absorption in the patients [4,8] and may have mediated a transfer of bone mineral from the peripheral to the axial skeleton [9]. It also gave rise to an increase in indices of bone resorption, as well as bone formation, in both iliac trabecular bone and in the skeleton as a whole.…”
Section: Introductionsupporting
confidence: 81%
“…Further experience has confirmed that this trend is statistically highly significant [5]; and similar results were seen in normal greyhounds given the same treatment [6]. However, when given in this way alone, in contrast to our findings in dogs [7], hPTH 1-34 did not increase dietary calcium absorption in the patients [4,8] and may have mediated a transfer of bone mineral from the peripheral to the axial skeleton [9]. It also gave rise to an increase in indices of bone resorption, as well as bone formation, in both iliac trabecular bone and in the skeleton as a whole.…”
Section: Introductionsupporting
confidence: 81%
“…It is known that some peptide hormones stimulate when administered in an episodic fashion but are inhibitory when administered continuously (Belchetz et a/., 1978). The effect of exogenous hPTH 1-34 on human and canine renal 1 a-hydroxylase has been shown to be dependent on the mode of administration (Podbesek et al, 1984;Slovik et a/., 1984). While there is some evidence that amino-terminal PTH is secreted in a pulsatile manner (Segre, 1983) there are currently no data concerning the pattern of release of humoral material in hypercalcaemia of malignancy and oncogenic osteomalacia.…”
Section: Discussionmentioning
confidence: 99%
“…It has been well known that the continuous infusion of PTH1-34 is associated with a catabolic effect, but that an intermittent administration promotes an anabolic effect on bone [52,53,54]. The mechanism underlying the anabolic and catabolic effect of PTH1-34 on bone metabolism is still unclear.…”
Section: Pthmentioning
confidence: 99%